Application of catalytic Z-selective olefin metathesis in natural product synthesis - Werrel, S; Walker, J; Donohoe, T (Elsevier, 2015)
Over the last few years, a number of olefin metathesis catalysts have been disclosed that enable the synthesis of energetically disfavoured Z-alkenes. The application of this method to the synthesis of complex natural products has driven the development of new catalysts and furthered the understanding of their behaviour and reactivity. This digest discusses the progress made and highlights the benefits of this chemistry over more traditional protocols.